Career development : a human resource development perspective - McDonald, Kimberly; Hite, Linda (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Career Development: A Human Resource Development Perspective offers a strategic framework that demonstrates the role of career development within the human resource function. It goes beyond conventional interventions, providing an interdisciplinary perspective inclusive of occupational psychology and career guidance theory, for an expansive and inclusive understanding of the topic. Historically, the career development literature has been viewed either from the perspective of the individual or from an economic perspective. As with the previous edition, McDonald and Hite bring together the strengths of both traditions, offering an integrated framework for career development. However, this newly updated edition also includes: Fresh cases, potentially from contributing practitioners An expanded final chapter on ethical and social justice issues More diverse examples highlighting differences between minority groups Reflective questions at the end of each chapter Implications for practice at the end of each chapter New coverage of emerging topics like resilience, career identity, career shocks, psychology of working theory, the gig economy, technology-rich environments and the impact of COVID on career development. This book will help prepare human resource development students, scholars, and practitioners to develop and maintain successful career development programs, and to foster more innovative research that advances the discourse"--
Keywords: Career development; Personnel management; BUSINESS & ECONOMICS / Careers / General; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Labor